The low-temperature method for study of coniferous tissues in the environmental scanning electron microscope - Neděla, Vilém; Tihlaříková, Eva; Hřib, Jiří (Microscopy research and technique, 2015)
The use of non-standard low-temperature conditions in environmental scanning electron microscopy might be promising for the observation of coniferous tissues in their native state. This study is aimed to analyse and evaluate the method based on the principle of low-temperature sample stabilization. We demonstrate that the upper mucous layer is sublimed and a microstructure of the sample surface can be observed with higher resolution at lower gas pressure conditions, thanks to a low-temperature method. An influence of the low-temperature method on sample stability was also studied. The results indicate that high-moisture conditions are not suitable for this method and often cause the collapse of samples. The potential improvement of stability to beam damage has been demonstrated by long-time observation at different operation parameters. We finally show high applicability of the low-temperature method on different types of conifers and Oxalis acetosella.
Keywords: Extracellular Matrix; cévnaté rostliny; mikroskopie elektronová rastrovací; Microscopy, Electron, Scanning; nízká teplota; Cold Temperature; Tracheophyta; extracelulární matrix